Understanding Community Norms Surrounding Tobacco Sales - McDaniel, Patricia A. (Public Library of Science, 2014)
BACKGROUND: In the US, denormalizing tobacco use is key to tobacco control; less attention has been paid to denormalizing tobacco sales. However, some localities have placed limits on the number and type of retailers who may sell tobacco, and some retailers have abandoned tobacco sales voluntarily. Understanding community norms surrounding tobacco sales may help accelerate tobacco denormalization. METHODS: We conducted 15 focus groups with customers of California, New York, and Ohio retailers who had voluntarily discontinued tobacco sales to examine normative assumptions about where cigarettes should or should not be sold, voluntary decisions to discontinue tobacco sales, and government limits on such sales. RESULTS: Groups in all three states generally agreed that grocery stores that sold healthy products should not sell tobacco; California groups saw pharmacies similarly, while this was a minority opinion in the other two states. Convenience stores were regarded as a natural place to sell tobacco. In each state, it was regarded as normal and commendable for some stores to want to stop selling tobacco, although few participants could imagine convenience stores doing so. Views on government's role in setting limits on tobacco sales varied, with California and New York participants generally expressing support for restrictions, and Ohio participants expressing opposition. However, even those who expressed opposition did not approve of tobacco sales in all possible venues. Banning tobacco sales entirely was not yet normative. CONCLUSION: Limiting the ubiquitous availability of tobacco sales is key to ending the tobacco epidemic. Some limits on tobacco sales appear to be normative from the perspective of community members; it may be possible to shift norms further by problematizing the ubiquitous presence of cigarettes and drawing connections to other products already subject to restrictions.